2014
DOI: 10.1024/0301-1526/a000362
|View full text |Cite
|
Sign up to set email alerts
|

Impact of compression stockings on calf-vein diameters and on quality of life parameters in subjects with painful legs

Abstract: Intra - individually tested the calf muscle vein diameters decrease under compression, more pronounced in the prone than in the standing position. In the ankle area the PTV does not decrease in standing subjects. Quality of life assessed increases for both compression stockings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
0
10
0
3
Order By: Relevance
“…C. Jeanneret-Gris и соавт. [4] в 2014 г. установили, что после 2 нед ношения трикотажа 2-го класса пациентами с жалобами на венозную боль происходит значимое уменьшение диаметра мышечных вен голени и малой подкожной вены, но калибр БПВ и ЗББВ не меняется.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…C. Jeanneret-Gris и соавт. [4] в 2014 г. установили, что после 2 нед ношения трикотажа 2-го класса пациентами с жалобами на венозную боль происходит значимое уменьшение диаметра мышечных вен голени и малой подкожной вены, но калибр БПВ и ЗББВ не меняется.…”
Section: Discussionunclassified
“…[3] и C. Jeanneret-Gris и соавт. [4] сокращение про- Ограничения исследования. Наше исследование имеет несколько значительных ограничений.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Two-thirds of them develop a mild form and less than 5 % of patients a severe form with skin ulcerations [4]. The authors of three systematic reviews with meta-analyses published within the last decade have concluded that compression stockings reduce the risk of developing PTS by about 50 % [3,5]. The authors of the current guidelines have adopted these conclusions and recommend compression stockings in patients with DVT [8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the focus has to be placed on the prevention of the possible long-term sequelae of DVT. The major preventive measure recommended today is the regular wearing of compression stockings [3]. For the prevention of PTS, some promising results of catheter-directed thrombolysis (CDT) have been published, but further studies are needed [1,2].…”
Section: Introductionmentioning
confidence: 99%